Measuring the effect of GST towards performances of Malaysian takaful operators - Che Mohd Salleh, Marhanum; Chowdhury, Mohammad Abdul Matin; Cahyono, Eko Fajar; Widiastuti, Tika (Emerald Publishing, 2022)
Purpose The main purpose of this study is to evaluate the performance of takaful operators in Malaysia.